Frequency of various risk factors and their correlation with outcome in complete heart block patients coming to a tertiary care hospital - Shabbir, Faizania; Rehman, Irum; Rajput, Tausif Ahmed; Raja, Tanveer Ahmed (Pakistan Journal of Physiology, 2020)
Objective: To determine the frequency of various risk factors and their correlation with outcome in patients having complete heart block. Methods: This Prospective cohort study was conducted at Rawalpindi Institute of Cardiology, Rawalpindi for a duration of six months. A total of 153 patients from both genders having complete heart block coming to Rawalpindi Institute of Cardiology were recruited in the study. The patients included in the study were evaluated for aetiology of complete heart block by history, physical examination, electrocardiography, blood tests, chest X-ray and echocardiography. A proforma was designed and filled by duty doctor for each patient. The proforma included demographic details, risk factors, presenting complaints, vitals and other parameters. The outcome of these patients (pacemaker implantation/medical treatment/death) was determined in the later part of the study and recorded on proforma. Results: Hypertension was the most common risk factor (43.8%) observed in patients of complete heart block in our study. There was no significant difference in the outcome in patients having risk factor of hypertension and smoking. However, a significant difference was observed in frequency of pacemaker implantation in diabetics as compared to non-diabetics (p=0.039). Conclusions: Hypertension was present in majority of complete heart block patients. The outcome however was not affected by most of risk factors. Only in diabetic risk factor group, significantly fewer numbers of patients were implanted with pacemaker. Death was also not significantly correlated with any particular risk factor. Pak J Physiol 2020;16(2):26?9